Examining Ibn Arabi’s Kashf Method on the Authenticity of Hadith - Afabih, Abdillah; Junianto, Viki (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2022)
The method of criticism of Hadith (Naqd Hadith) was developed by Hadith experts to prove whether a Hadith can be categorized as coming from the Prophet or not. Hadith scholars tend to use the method of sanad criticism (Naqd al-Sanad) in determining the authenticity of Hadith. Over time the Hadith scholars began to come up with new methods in an effort to determine the authenticity of hadith in accordance with its scientific tendencies, one of these methods was the Kashf method. This method is widely known among Sufis, but has not been widely used in the context of hadith criticism. One of the Sufi figures who had a focus on the Kashf method was Ibn Arabi. This study is a literature review by analyzing documents derived from Ibn Arabi and experts related to the Kashf method. Data is analyzed by applying descriptive analytical methods and using philosophy of science to determine the validity of the Kashf Method as a method of criticism of Hadith. This study shows that the Kashf method is a mu’tabar (authoritative) method for Sufi scholars and is also recognized by some Hadith experts. According to Zabid al-Jabiri in the treasures of Islamic philosophy, there are three models of methodology of thought, namely bayani, burhani, and irfani. Kashf method includes the irfani model. irfani can be interpreted as the disclosure of knowledge obtained through irradiation of essence by God to His servant (Kashf) after doing spiritual practice (riyâdlah) done on the basis of love. Therefore, the Kashf method is one of the valid methods for determining the validity of hadith.